Genetic variants within obesity-related genes are associated with tumor recurrence in patients with stages II/III colon cancer. Issue 1 (January 2015) - Sebio, Ana; Gerger, Armin; Matsusaka, Satoshi; Yang, Dongyun; Zhang, Wu; Stremitzer, Stefan; Stintzing, Sebastian; Sunakawa, Yu; Yamauchi, Shinichi; Ning, Yan; Fujimoto, Yoshiya; Ueno, Masashi; et al.
<x xml:space="preserve">Abstract</x> Objective Obesity is an established risk factor for colorectal cancer (CRC) incidence and it is also linked to CRC recurrence and survival. Polymorphisms located in obesity-related genes are associated with an increased risk of developing several cancer types including CRC. We evaluated whether single-nucleotide polymorphisms in obesity-related genes may predict tumor recurrence in colon cancer patients. Materials and methods Genotypes were obtained from germline DNA from 207 patients with stage II or III colon cancer at the Norris Comprehensive Cancer Center. Nine polymorphisms in eight obesity-related genes (PPAR, LEP, NFKB, CD36, DRG1, NGAL, REGIA, and DSCR1) were evaluated. The primary endpoint of the study was the 3-year recurrence rate. Positive associations were also tested in an independent Japanese cohort of 350 stage III CRC patients. Results In univariate analysis, for PPARrs1801282, patients with a CC genotype had significantly lower recurrence probability (29±4% SE) compared with patients with a CG genotype (48±8% SE) [hazard ratio (HR): 1.77; 95% confidence interval (CI), 1.01–3.10; P=0.040]. For DSCR1rs6517239, patients with an AA genotype had higher recurrence probability than patients carrying at least one allele G (37±4% SE vs. 15±6% SE) (HR: 0.51; 95% CI, 0.27–0.94; P=0.027). This association was stronger in the patients bearing a left-sided tumor (HR: 0.34; 95% CI, 0.13–0.88; P=0.018). In the Japanese cohort, no associations were found. Conclusion This hypothesis-generating study suggests a potential influence of polymorphisms within obesity-related genes in the recurrence probability of colon cancer. These interesting results should be evaluated further.